DEMOKRASI DI INDONESIA Antara Pembatasan dan Kebebasan Beragama - Abu Hafsin (Balai Penelitian dan Pengembangan Agama Semarang, 2010)
Democracy has been understood differently. Law no.1/PNPS/1965 whichis previously recognized as protection of religious followers is recognized aslimitation that denied principle of democracy recently. The polemic of religiousfreedom ended with proposal of judicial review on law no.1/PNPS/1965 proposedby some group of societies. This proposal, finally, is rejected by primecourt. This rejection can be corrected since UUD 1945 follows an expressiverelativism on religious freedom. Because of the existence of ambiguous wordsin such law, revision is really needed so that there will be a clear explanationrelated to who has the authority to determine whether certain religious teachingis wrong or not. It is important to solve the problematic matters faced by government and certain religious groups.Keywords : demokrasi, relativisme